Conservative Management of Pott's Spine and Its Outcome: An Institute-Based Observational Study - Jiwani, Rahil; Ghosh, Sourabh; Giri, Shubham (International Journal of Integrated Health Sciences, 2023)
Objective: To analyze the functional outcome of cases with Pott’s disease treated solely by antitubercular drugs.Methods: This observational study was conducted at the Department of Orthopedics of a tertiary care medical college. Sixty patients with Pott’s disease were included in this study based on predefined inclusion and exclusion criteria. All patients received antitubercular drugs for nine months. The Modified McCormick Scale (MSS) was used to assess the outcome of patients.Results: Out of 60 patients, 37 (61.67%) were females, and 23 (38.33%) were males, with an M: F ratio of 1:0.62. Most patients had some or the other risk factors and belonged to low socioeconomic status. The most common presenting complaint was low back pain, and the thoracolumbar spine was most commonly involved. There was a significant improvement in the patient’s functional status as assessed by the MSS score.Conclusion: If diagnosed early, patients with Pott’s disease can be treated solely by antitubercular treatment with excellent outcomes.